Correct Handwashing Education According to WHO Guidelines at MI Muhammadiyah Needs Magelang District - Ika Afifah Nugraheni; Hapsari Wahyuningsih (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
At the beginning of 2020, the world was shocked by the emergence of a new disease outbreak, Covid-19, which was caused by the SARS COV-2 virus. The school environment is one of the places that is vulnerable to the spread of this virus. An effective preventive measure against the spread of Covid-19 is the application of clean and healthy living habits (PHBS) in the school environment, one of which is the habit of washing hands. However, not all residents in the school understand how to wash their hands properly. The purpose of this service activity is to provide education about proper hands washing according to WHO for MI Muhammadiyah Need in Magelang Regency. The material needed for the implementation of the activity is a hand sanitizer liquid made from 70% active alcohol as a hand disinfectant. Implementation of community service activities using demonstration methods and hands-on practice of hands washing according to WHO. Based on this service activity, not all members of the MI Muhammadiyah Need was known the steps for hands washing properly according to WHO. Through this service, school residents are given knowledge and practice the 8 steps of hand washing according to WHO using a handsanitizer. Thus, school residents are expected to be able to apply proper hand washing methods in their daily life and socialize it to other individuals school residents are given knowledge and practice the 8 steps of hand washing according to WHO using a handsanitizer. Thus, school residents are expected to be able to apply proper hand washing methods in their daily life and socialize it to other individuals school residents are given knowledge and practice the 8 steps of hand washing according to WHO using a handsanitizer. Thus, school residents are expected to be able to apply proper hand washing methods in their daily life and socialize it to other individuals